Textbook of diagnostic microbiology - Lehman, Donald C.; Manuselis, George (Maryland Heights, Mo. : Saunders/Elsevier, 2011)
Introduction to clinical microbiology -- Laboratory identification of significant isolates -- Laboratory diagnosis of infectious diseases: an organ system approach to diagnostic microbiology.
Includes bibliographical references and index.
Keywords: Diagnostic microbiology; Microbiological Techniques; Communicable Diseases -- diagnosis. Laboratory Techniques and Procedures